PENGARUH PROFITABILITAS, CAPITAL INTENSITY, INVENTORY INTENSITY TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR MANUFAKTUR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Diva Aura Assyfa; Kholidiah Kholidiah (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the influence of profitabilitas, capital intensity, inventory intensity on food and beverage manufacturing sector companies listed on the Indonesia Stock Exchange (IDX). Tax avoidance is the practice of legally managing tax obligations by exploiting existing tax regulations to reduce the tax burden that must be paid. This study uses a quantitative approach with a causal associative research type. The sampling technique used is purposive sampling, namely all food an beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the consecutive research period, namely 2020-2024. The analysis process was carried out using SPSS software. The results of the study indicated that profitabilitas, capital intensity, inventory intensity do not have a significant effect on tax avoidance. This finding indicates that level of influenced by other factorcs outside the research model.